The Organization and Control of Intra-Limb Anticipatory Postural Adjustments and Their Role in Movement Performance - Cavallari, Paolo; Bolzoni, Francesco; Bruttini, Carlo; Esposti, Roberto (Frontiers in Human Neuroscience, 2016)
Anticipatory Postural Adjustments (APAs) are commonly described as unconscious muscular activities aimed to counterbalance the perturbation caused by the primary movement, so as to ensure the whole-body balance, as well as contributing to initiate the displacement of the body centre of mass when starting gait or whole-body reaching movements. These activities usually create one or more fixation chains which spread over several muscles of different limbs, and may be thus called inter-limb APAs. However, it has been reported that APAs also precede voluntary movements involving tiny masses, like a flexion/extension of the wrist or even a brisk flexion of the index-finger. In particular, such movements are preceded by an intra-limb APA chain, that involves muscles acting on the proximal joints. Considering the small mass of the moving segments, it is unlikely that the ensuing perturbation could threaten the whole body balance, so that it is interesting to enquire the physiological role of intra-limb APAs and their organization and control compared to inter-limb APAs. This review is focused on intra-limb APAs and highlights a strict correspondence in their behaviour and temporal/spatial organization with respect to inter-limb APAs. Hence it is suggested that both are manifestations of the same phenomenon. Particular emphasis is given to intra-limb APAs preceding index finger flexion, because their relatively simple biomechanics and the fact that muscular actions were limited to a single arm allowed peculiar investigations, leading to important conclusions. Indeed, such paradigm provided evidence that by granting a proper fixation of those body segments proximal to the moving one APAs are involved in refining movement precision, and also that APAs and prime mover activation are driven by a shared motor command.